2020
DOI: 10.1016/j.freeradbiomed.2019.12.022
|View full text |Cite
|
Sign up to set email alerts
|

How the redox state regulates immunity

Abstract: This document is made available in accordance with publisher policies and may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the URL above for details on accessing the published version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 180 publications
(203 reference statements)
0
42
0
3
Order By: Relevance
“…The system is highly flexible and tunable, providing redox modulation that is dependent on actual needs. The other way around, glucose flows and redox state regulate the function of immune system[121]. Failure of feedback loops and distorted signaling-either from CNS (stress), the immune system (inflammation) or the malfunction of peripheral sensors-lead to excessive, uncontrolled (poorly controlled) glucose release and/or the activation of gluconeogenesis, leading to diabetes.…”
mentioning
confidence: 99%
“…The system is highly flexible and tunable, providing redox modulation that is dependent on actual needs. The other way around, glucose flows and redox state regulate the function of immune system[121]. Failure of feedback loops and distorted signaling-either from CNS (stress), the immune system (inflammation) or the malfunction of peripheral sensors-lead to excessive, uncontrolled (poorly controlled) glucose release and/or the activation of gluconeogenesis, leading to diabetes.…”
mentioning
confidence: 99%
“…Multiple evidence showed that ROS are involved in sensing danger, that is, the presence of pathogens as well as tissue damage. Indeed, Pathogen-Associated Molecular Patterns (PAMPs) and Damage-Associated Molecular Patterns (DAMPs) recognition by immune cells can trigger intracellular signaling events leading to increased ROS generation that can result in inflammasome activation and pro-inflammatory cytokine production [ 3 , 4 ]. ROS play also a critical regulatory role in determining the initiation and outcome of phagocytosis.…”
Section: Reactive Oxygen Species Role In Immunitymentioning
confidence: 99%
“…Indeed, ROS production is recognized as necessary for all stages of the inflammatory process. Both innate and adaptive immunity entail redox-regulated processes, for instance, the governance of immune cells infiltration, their activation and differentiation, the oxidative burst of phagocytes, as well as the control of cellular signal transduction and transcription programs [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The regulatory effect of oxidants on immunity was first evidenced when hydrogen peroxide at micromolar concentrations was able to activate the transcription factor nuclear factor-κB (NF-κB), a key determinant of the immune response; this effect was largely missing after a co-treatment with the antioxidant N-acetylcysteine (Schreck et al, 1991). Since then, several investigations addressed the immune-regulatory properties of oxidants in mild concentration, but also of oxidoreductant enzymes (Mullen et al, 2019).…”
Section: Cholestasismentioning
confidence: 99%